Identification Of Clinostomum sp. Parasites In Swamp Sepat Fish (Trichogaster trichopterus) In FAPERIKA DAM, Pekanbaru - Nasution, Ahmad Tirmizi; Lukistyowati, Iesje; Riauwaty, Morina (Jurnal Akuakultur SEBATIN, 2023)
Parasites are organisms that live on other organisms that can benefit from the symbiosis, while the host is harmed. This research was conducted from March to Mei 2022 at the Laboratory of Fish Parasites and Diseases, Department of Aquaculture, Faculty of Fisheries and Marine. Trichogaster trichopterus sampling was carried out Feperika Dam, Pekanbaru. The aim of the study was to obtain the prevalence and intensity of the parasite Clinostomum sp. which infects the swamp fish (Trichogaster trichopterus) in Faperika Dam, Pekanbaru. The method used is a survey method and direct observation of the sample. Sampling was carried out three times with sampling points consisting of 3 places, namely: Location 1 is at the entrance of the reservoir, locations 2 and 3 are located to the west and north of location 1 with a distance of each location 50 meters. The results of the identification showed that the sample of bog fish infected with trematode parasites was Clinostomum sp. with prevalence ranging from 93.9-100%, prevalence in locations 1 and 2 (100%), and intensity for each location, namely, at location 1 at 36.9 ind/bird, location 2 at 41.3 ind and location 3 is 34.3 ind.